POSITIVE MENTAL HEALTH SURVEILLANCE INDICATOR FRAMEWORK QUICK STATS, YOUTH (12 TO 17 YEARS OF AGE), CANADA, 2017 EDITION (Health Promot Chronic Dis Prev Can, 2017)
Positive mental health is a state of well-being that allows people to feel, think and act in ways that enhance the ability to enjoy life and deal with challenges.1 The Positive Mental Health Surveillance Indicator Framework (“the Framework”) provides comprehensive, high quality information on the outcomes and risk and protective factors associated with positive mental health across four domains (individual, family, community and society), to support research and policy development. The release of the Framework for youth aged 12 to 17 years is the second in a series; the Framework for adults aged 18 years and older was released in early 2016.2 The Framework was developed in consultation with stakeholders working in mental health surveillance, programs and policy. The details of the development of the Frameworks across the life course, for adults, youth and children, can be found in the paper “Monitoring positive mental health and its determinants.”3 More data on positive mental health can be found online using the Public Health Agency of Canada’s interactive data tool, “Infobase.”4